Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Susu Jahe di DeeSuHe - Novalina, Noura; Syahputra, Sakti (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2024)
This study aims to determine how much effect of product quality and price oninterest in buying ginger milk in DeeSuHe. This research background with the negative review on comments on Instagram ginger milk DeeSuHe where buyers who buy ginger milk declare quality ginger products are quite good, but there are constraints on the packaging the product is a cup lid that is not tight so it often spills and also complain about the price paid is not comparable with what buyers expect as usual. Methods research used is quantitative methods with techniques data collection using questionnaires and QobsQervations. The population in this study are the buyers who buy Ginger milk in DeeSuHe. Number of samples successfully processed using the slovin formula is as much as 101 people bought ginger milk in DeeSuHe. Data analysis techniques in this study uses validity test, classical assumption test, and multiple linear regression analysis with t test and F test. Then the data is processed using IBM SPSS software program 21. The result of the coefficient of determination (R2) this study shows partially independent variables affect the decision stay (dependent variable) is the product quality positif amounted to 97.2% with a value of t count 6.239 > t table 1.988 with significance value of 0.000 < 0.05 and the price of a positive effect amounted to 97.3% with a value of t count 12.666 > t table 1.988 with significance value 0.000 < 0.05. Simultaneously product quality and price has a positive effect on buying interest with the value of F count 1694.668 > F table 49.5 with a significance value of 0.000 < 0.05 and the coefficient of determination (R2 a) product quality and price amounted to 97.1%, while the remaining 2.9% influenced by variablesothers were not included in the study.